P I – 3–2 Association of maternal diet during pregnancy and metabolite profile in cord blood. (18th March 2018) - Ramlochansingh, Carlana; Harris, Carla; Uhl, Olaf; Demmelmair, Hans; Heinrich, Joachim; Standl, Marie; Koletzko, Berthold; Thiering, Elisabeth
Abstract : Background/aim: Maternal diet before and during pregnancy can contribute to an offspring's mental and physical health. Moreover, maternal food intake can modulate overweight or obesity issues and the development of adverse metabolic related outcomes/diseases later in life. Thus, this study aims to evaluate the association of maternal diet during pregnancy with the metabolite profile in cord blood. Methods: An analysis of maternal diet was conducted to study diet variability and patterns and to derive a set of factors, which would then be used in association analyses with cord blood metabolites. These analyses were done in the German LISA birth cohort (n 650 with information available on maternal diet and cord blood metabolome). Maternal food intake during the last 4 weeks of pregnancy was assessed by using a semi-quantitative food-frequency questionnaire (FFQ) comprising of 45 food items administered shortly after childbirth. Glycerophospholipid fatty acids (GPL-FA), polar lipids, non-esterified fatty acids (NEFA), and amino acids were analysed with gas chromatography (GPL-FA) or targeted liquid chromatography-tandem mass spectrometry based metabolomics platforms. Results: Factor analysis shows ten factors accounting for 28% of the total variance that could be classified into different dietary patterns. Some of the categories are 'meat-eaters', 'healthy/vegetable-eaters' and 'sweet-eaters' additionally a seasonal pattern in some maternal diets has emerged. A regression score is used in an effort to provide the highest correlations between the factor and its score. Finally, a linear regression for association with cord blood metabolites, adjusted for relevant confounders, will complete the investigation. Conclusion: A good classification of the different maternal diets has been identified which allows for the characterisation of associations between maternal diet and cord blood metabolites. We conclude that maternal diet modulates metabolic status of the fetus which may be relevant for fetal growth and development.